Risk factors for spontaneous localized intestinal perforation in the preterm infant. (2nd October 2018) - Rayyan, Maissa; Myatchin, Ivan; Naulaers, Gunnar; Ali Said, Yasmin; Allegaert, Karel; Miserez, Marc
Abstract: Purpose: The aim of this study was to investigate prenatal and postnatal risk factors for spontaneous intestinal perforation (SIP) in preterm infants. Material and methods: Matched case-control study of 62 preterm infants (matching based on gender, gestational age and birth weight) who developed a SIP over a period of 20 years in a single NICU. Univariate and multivariate logistic regression analysis were performed. Results: Prenatal risk factors were not significantly different between cases and controls. Patients exposed to surfactant and inotropic agents have an increased risk for SIP. No initiation of feeding before development of SIP and IVH ≥ grade 3 were also associated with an increased risk for SIP. In multivariate analysis inotropic agents, lack of initiation of feeding and IVH ≥ grade 3 remained significant risk factors (OR 5.58 (95% CI 1.14–27.22), 0.29 (95% CI 0.09–0.88), 15.2 (95% CI 1.09–211.55) respectively). Conclusions: The study found that patients with SIP are more likely to have been exposed to inotropic agents and to have developed IVH ≥ grade 3. They were also less likely to have been fed. These risk factors most likely reflect the severity of illness of preterm infants and an increased vulnerability for developing SIP.